Music and Politics in San Francisco : From the 1906 Quake to the Second World War. - Miller, Leta E. (California studies in 20th-century music ;, 2011)
This lively history immerses the reader in San Francisco's musical life during the first half of the twentieth century, showing how a fractious community overcame virulent partisanship to establish cultural monuments such as the San Francisco Symphony (1911) and Opera (1923). Leta E. Miller draws on primary source material and first-hand knowledge of the music to argue that a utopian vision counterbalanced partisan interests and inspired cultural endeavors, including the San Francisco Conservatory, two world fairs, and America's first municipally owned opera house. Miller demonstrates that ram.